The Web of Science database as a source of information on Open Access publications from the Czech Republic and Poland - Rychlik, Małgorzata (My University, 2018)
This paper aims to present the Web of Science database as an important source of information on Open Access publications. The indirect goal of the study was to examine whether there were any differences between scholars and researchers from the Czech Republic and Poland in open publishing and, if so, to what degree? Methods: the first stage of the study involved data extraction from the WoS CC database of publications that dealt primarily with OA publishing. The data included 9,244 publications from Poland and 3,870 publications from the Czech Republic published in 2013. For both countries under scrutiny, the following comparisons were made: type of documents, language of publication, the most popular research areas in OA and bibliometric indicators (citations and H-index). In addition, the productivity of scholars from both countries was juxtaposed and compared (the supporting statistical data was provided by OECD). The data covering the period 2010-2016 was also analysed to examine the number of works published in OA in Poland and the Czech Republic. The second stage involved extraction of the altmetric indicators for most highly cited works from both countries, and their further comparison. For this particular study, the Altmetric Explorer was used. Results: it has been proved that the resources of the WoS CC database provide convenient data environment for different analyses, both qualitative and quantitative, and, additionally, provide a strong predictive value in defining future trends in open access publishing.
Keywords: Web of Science; Unpaywall; Open Access